Analisis Sistem Informasi Akuntansi (SIA) Pelayanan Jasa Rawat Inap Dalam Menunjang Efektivitas Pengendalian Internal Pendapatan Rumah Sakit Umum (RSU) Haji Kota Medan - Denisa Felia Putri Munthe; Marliyah Marliyah; Kusmilawaty Kusmilawaty (BADAN PENERBIT STIEPARI PRESS, 2024)
This study aims to analyze the accounting information system for inpatient services in supporting the effectiveness of internal control of revenue of the Medan City Haji General Hospital (RSU). An accounting information system is a set of resources such as people and equipment, designed to convert financial and other data into information. An adequate accounting information system can improve internal control of hospital revenue, by providing accurate and timely information, and ensuring the security and confidentiality of patient data and hospital financial information. This research uses qualitative research methods with a descriptive approach. Data sources obtained with primary data and secondary data collected by researchers by conducting observation techniques, interviews, and literature reviews related to the accounting information system for inpatient services in supporting the effectiveness of internal control of revenue. The results of this study concluded that after analyzing the accounting information system at the Haji General Hospital (RSU) Medan City has been running well and plays an effective role in improving the internal control of hospital revenue although sometimes it still experiences system disruptions so it needs to be improved again and the internal control run by the Haji General Hospital (RSU) Medan City has been effective.